Integrasi Edukasi Kesehatan dan Senam Komunitas sebagai Upaya Nonfarmakologis Pengendalian Hipertensi dan Diabetes Mellitus - Wijayanti, Wijayanti; Wianti, Sri; Lismayanti, Lilis; Haq, Zhalifunnas ’Abud Dhiyaul (Yayasan Inspirasi El Burhani, 2025)
Introduction: Hypertension and diabetes mellitus (DM) are prevalent chronic diseases that contribute significantly to morbidity and mortality, particularly in Indonesia. These conditions often coexist, exacerbating the risk of cardiovascular diseases and chronic kidney disease. Objective: This community service aimed to integrate interactive visual health education with community-based exercise (senam) as a non-pharmacological approach to manage hypertension and DM in Jayengan, Surakarta. The goal was to improve participants' knowledge and promote long-term healthy behavior changes. Method: The program was implemented with 30 participants from Jayengan, using a quasi-experimental pre-post design. Participants were given health education through animated videos and engaged in 30-minute community exercise sessions. Knowledge assessments were conducted using a pre- and post-test to measure changes in knowledge related to hypertension and DM. Result: The intervention significantly increased participants’ knowledge. Before the program, 90% of participants had low knowledge, while after the intervention, 96.7% had high knowledge, with an average score increase from 7.33 to 13.13. Additionally, participants reported increased engagement in regular physical activity, with a high willingness to continue the exercise routine independently. Conclusion: Integrating visual health education with community exercise proved to be an effective strategy for enhancing participants’ knowledge and encouraging healthy lifestyle changes. The approach not only strengthened health literacy but also fostered community engagement in self-care practices. Given its success, this model has the potential for sustainable, scalable implementation in other communities for the management of hypertension and DM.